FORMATION OF NEW CULTURAL IDENTITY ELEMENTS OF THE NORTH CAUCASUS PEOPLES (BASED ON THE MATERIALS OF THE TEREK REGION OF THE 2ND HALF OF XIX CENTURY – BEGINNING OF XX CENTURY) - Tatyana Evgenyevna Pokotilova (Вестник Северо-Кавказского федерального университета)
The article investigates the process of conscious acceptance of certain elements of new consciousness, norms and values by the peoples of the North Caucasus under conditions of their affiliation with the Russian Empire and modernization processes experienced by pre-revolutionary Russia.